(Re)articulating writing assessment for teaching and learning - Huot, Brian A. (Utah State University Press, 2002)
Brian Huot's aim for this book is both ambitious and provocative. He wants to reorient composition studies' view of writing assessment. To accomplish this, he not only has to inspire the field to perceive assessment?generally not the most appreciated area of study?as deeply significant to theory and pedagogy, he also has to counter some common misconceptions about the history of assessment in writing.